Breast Reduction for Fibrocystic Breast Disease: a case report (Community Based Medical Journal, 2018)
The pathophysiology of fibrocystic breast disease is determined by estrogen predominance that results in hyper proliferation of connective tissue (fibrosis), the risk of breast cancer is increased twofold to fourfold in these patients. The clinical correlate of fibrocystic disease is reflected by breast and axillary pain or tenderness. The disease progresses with advancing premenopausal age and is most pronounced in women during their 40s. We present a case of 23 years old lady who completely get rid of her symptoms from heavy breast with diagnosed fibrocystic changes immediately after breast reduction surgery. Breast reduction can be a treatment option for fibrocystic breast diseases which are not responding to medical treatment.CBMJ 2018 July: Vol. 07 No. 02 P: 42-44